PENGARUH FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN SUMEDANG - Shofwan Hendryawan; Meva Kemala Ismanghaniyah; Moch. Willy Wildan; Ricky Fhauzi Hermawan; Yayang Nugraha (Journal Of Regional Public Administration (JRPA), 2020)
This study aims to determine the effects of work facilities on employee productivity at Central Bureau of Statistics of Sumedang District. The method used in this study is a quantitative research method which is used to answer a predetermined hypothesis. In this study, researchers used inferential descriptive data analysis technique that describe collected data and make conclusions that are applicable generally. The sampling technique used in this study is saturation sampling technique which involves the entire population to be respondents. Based on the results of the study, researchers obtained information that the availability of work facilities in Central Bureau of Statistics of Sumedang District reached 82% and the score was categorized very good, as good as the work productivity of employee in Central Bureau of Statistics of Sumedang District reached 90% with a very good category. The correlation of work facilities with employee productivity at Central Bureau of Statistics of Sumedang District with a correlation coefficient reached 0.591 is in medium category. The effects of work facilities on employee productivity at Central Bureau of Statistics of Sumedang District is 35% while 65% is influenced by other factors not researched in this study.